Estratégias para o restabelecimento de áreas antropizadas com espécies arbóreas nativas no extremo sul do bioma Mata Atlântica - Rorato, Daniele Guarienti (2017)
The aim of this research was to characterize the development of Casearia sylvestris, Cupania vernalis, Eugenia involucrata, Inga vera, Parapiptadenia rigida and Schinus terebinthifolius in relation to the incidence of frost and the use of different silvicultural practices in altered areas in the South Atlantic Forest Biome. The planting was carried out in Nova Palma, RS, in two riparian areas. In the first experiment, the treatments were distributed in a factorial design (2 x 2) [two types of containers (180 cm3 polypropylene conical tubes and 1.500 cm3 polyethylene bags)], and presence or absence of green manure (Canavalia ensiformis and Vicia sativa)]. In the second experiment, factorial design (3 x 2) was used, considering two types of fertilization and control (chemical fertilization, organic fertilization and absence of fertilization) x soil cover (presence or absence of mulching). In both experiments, survival, morphological attributes (height, steam diameter, tree canopy, shoot dry weight and leaf area) and physiological (chlorophyll a fluorescence, chlorophyll a, chlorophyll b and carotenoid content, acid phosphatase, soluble phosphorus content, superoxide dismutase and hydrogen peroxide) were evaluated. During 2014 winter season, the damage from the impact of frost was assessed through a rating scale ranging from 0 (100% of the leaf area and damaged stem) to 10 (no visual damage). It was also evaluated the potential of growth recover species, characterized as resilience. In addition, soil physical parameters in the experimental and adjacent areas were evaluated at the end of the study, at 720 and 900 days after planting (experiment 1 and 2, respectively). The forest species respond differently to frost incidence. C. sylvestris, E. involucrata, P. rigida and S. terebinthifolius were tolerant to frost and/or showed potential for growth recovery, on the other hand, C. vernalis and I. vera were more sensitive to frost, with high mortality rates and/or no resilience potential. Survival rate was higher than 77%, regardless of the factors tested, except for C. vernalis (61%) and E. involucrata (80%) that showed higher survival when mulching was used on the soil. The species presented higher growth when they were produced in larger containers volume and with introduction of the green manure. In addition, chemical fertilization, through controlled release fertilizer, positively influenced the growth in the field, increasing the development of the seedlings, in order to minimize possible damages due biotic and/or abiotic stresses. The presence of mulching did not show any effect on the growth of all species analyzed. In a complementary way, analysis of the environments in the experimental areas evidenced improvements in the physical quality of the soil, contributing to the return of equilibrium of these ecosystems.